Molecular phylogenetic relationships of the lizard clade Liolaemus elongatus (Iguania: Liolaemini) with the description of a new species from an isolated volcanic peak in northern Patagonia - Avila, Luciano Javier (2015)
A new species of the Andean-Patagonian Liolaemus elongatus clade is described. Liolaemus crandalli sp. nov. differs from other members of its clade by a combination of coloration characters, scale counts and genetic traits. Liolaemus crandalli sp. nov. is known only from an isolated volcanic mountain in northwestern Patagonia above 1500 m.a.s.l. unconnected with other habitat suitable for species of the Liolaemus elongatus clade.